Designing zoning of remote sensing drones for urban applications: a review - Hj. Mohd. Noor, Norzailawati; Abdullah, Alias; Shairatul, Akma (International Society for Photogrammetry and Remote Sensing, 2016)
This paper discusses on-going research related to zoning regulation for the remote sensing drone in the urban applications. Timestamped maps are presented here follow a citation-based approach, where significant information is retrieved from the scientific literature. The emergence of drones in domestic air raises lots understandable issues on privacy, security and uncontrolled pervasive surveillance that require a careful and alternative solution. The effective solution is to adopt a privacy and property rights approach that create a drone zoning and clear drone legislatures. In providing a differential trend to other reviews, this paper is not limited to drones zoning and regulations, but also, discuss on trend remote sensing drones specification in designing a drone zones. Remote sensing drone will specific according to their features and performances; size and endurance, maximum airspeed and altitude level and particular references are made to the drones range. The implementation of laws zoning could lie with the urban planners whereby, a zoning for drone could become a new tactic used to specify areas, where drones could be used, will provide remedies for the harm that arise from drones, and act as a different against irresponsible behaviour. Finally, underlines the need for next regulations on guidelines and standards which can be used as a guidance for urban decision makers to control the drones’ operating, thus ensuring a quality and sustainability of resilience cities simultaneously encouraging the revolution of technology. 1.0 INTRODUCTION The innovation of drones’ technologies has challenged a new regulation on guidelines and standards in many development countries. A drone is a system that set of complementary technologies brought together with their own class to fulfil a specific task. The drone can range in size and form and are typically described according to weight, endurance, purpose of use and altitude of the operation. (Jenkins, 2015). According to Department of Civil Aviation (DCA), a small aircraft is defined as any unmanned aircraft weighing not more than 20kg. The drone has been served the needs of large-scale low-altitude imaging and geospatial information users and developing an industry of its own (Cho, et al., 2013; Mayr, 2013; and Petrie, 2013). The data retrieved by drones can be used quickly to provide up-to-date, area-wide and cost-effective transformation data or images into translatable information through mapping of the urban morphology (Jenkin, 2015). According to